2017
DOI: 10.2527/tas2017.0056
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of the lactation and milk yield and composition of selected breeds of sheep and goats

Abstract: The objective of this study was to characterize the milk yield (MY) and milk composition of relevant sheep and goat breeds raised around the world to be used with nutrition models for diet formulation and nutrient balancing. A 2-step approach was used. First, a database developed by the Food and Agriculture Organization was used to identify relevant breeds (i.e., frequently raised) by comparing the occurrence of transboundary breed names across countries. We selected transboundary breeds that occurred more tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 37 publications
(48 reference statements)
3
40
1
1
Order By: Relevance
“…Our analysis was highly accurate (Cb > 0.852 and RMSEP > 29%) in predicting milk yield according to the selected udder measurements, but the precision (r 2 < 0.632) was systematically low, resulting in under prediction (CD < 1.897) across equations. The variation in milk yield may be largely explained by environmental effects [6] or genotype [6,15,37]. Although the previous studies indicated that ewes rearing twin lambs had higher daily milk yields [6,38], because of low prolificacy in the present study (1.13), the effect of litter size could not be determined due to insufficient statistical power.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Our analysis was highly accurate (Cb > 0.852 and RMSEP > 29%) in predicting milk yield according to the selected udder measurements, but the precision (r 2 < 0.632) was systematically low, resulting in under prediction (CD < 1.897) across equations. The variation in milk yield may be largely explained by environmental effects [6] or genotype [6,15,37]. Although the previous studies indicated that ewes rearing twin lambs had higher daily milk yields [6,38], because of low prolificacy in the present study (1.13), the effect of litter size could not be determined due to insufficient statistical power.…”
Section: Discussioncontrasting
confidence: 56%
“…Among these indirect methods, udder measurements and the weight gain of lambs has been evaluated in addition to more sophisticated and expensive techniques, such as the dilution of isotopes [5,6,[12][13][14]. The need to correctly assess milk yield is important, but there is a chronic lack of information [15,16] and a lack of dissemination of available and accurate methods [10].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the values of ash (0.92%), lactose (4.43%), cryoscopy index (0.575°H) and titratable acidity (0.23 g of lactic acid/100 mL) ( Table 1) were similar of the means values described in others studies about sheep milk. (Merlin Junior et al, 2015;Rafiq et al, 2016;Balthazar et al, 2017;Ferro et al, 2017;Panayotov et al, 2018;Sobrino et al, 2018). In addition, the values of fat (6.28%), protein (5.30%) and TDM (16.52%) were lower ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…* analysis in triplicate /sample ** Source: (2015-2020) MerlinJunior et al, (2015);Rafiq et al, (2016);Balthazar et al, (2017);Ferro et al, (2017);Panayotov et al, (2018);Sobrino et al, (2018).…”
mentioning
confidence: 99%
“…The NRC (2001) of dairy cattle uses fat content of 4 % as a standard value of milk fat. Dairy ewes compared to the meat and wool sheep show distinct milk production, lactation peak, and milk composition (protein and fat) (Dove and Kelman, 2015;Ferro et al, 2017;Gonzalo et al, 1994;Massouras et al, 2018;Nudda et al, 2002;Park, 2007). In contrast to dairy cattle, an exact value has not been stipulated for dairy sheep to use as a standard value for sheep milk, but predictive equations for DMI take into account milk composition to assess the energy content of the milk.…”
Section: Prediction Of Dry Matter Intakementioning
confidence: 99%